Perioperative analgesic efficacy of quadratus lumborum block versus transversus abdominis plane block in dogs undergoing laparoscopic ovariectomy: a prospective randomized clinical trial - Fumanelli, Eleonora; Cocca, Giorgia; Giannetti, Giorgia; Parabella, Marianna; Rabozzi, Roberto; Sarotti, Diego (Frontiers in Veterinary Science, 2025)
IntroductionThis prospective randomized study (protocol number 0156185) aims to evaluate the perioperative analgesic efficacy of quadratus lumborum block (QLB) versus transversus abdominis plane block (TAPB) in dogs undergoing elective laparoscopic ovariectomy.Materials and methodsDogs premedicated with methadone (0.2 mg/kg IV), inducted with propofol and maintained under general anesthesia with isoflurane were randomized into 3 groups. In the QLB group, 0.5 mL/kg of ropivacaine 0.35% was administered at L1–L2 bilaterally; in the TAPB group, 0.25 mL/kg of ropivacaine 0.35% per injection was administered in four sites; the third group, named P, was a control group where dogs did not receive any block. Heart rate (HR), invasive mean arterial pressure (MAP) and end-tidal concentration of isoflurane (etISO) were recorded at surgical timepoints: pre-stimulus baseline (T0), skin and abdominal wall incision (T1), induction of capnoperitoneum (T2), traction and ligation of the right (T3) and left ovaries (T4). Intraoperative data collection and adjustment of the hypnotic plan were performed by an operator blinded to the used technique. Cardiovascular response (CR) was defined as a 20% increase in MAP and/or HR from T0. Dogs with MAP greater than 30% of baseline received an infusion of remifentanil (0.5 mcg/kg/min) and were recorded as intraoperative rescue analgesia (iRA) events. Postoperative analgesia was assessed with Glasgow Composite Measure Pain Scale short form (GCMPS-SF) at 2 and 4 h after extubating.ResultsThirty-two dogs were included and analyzed (12 in TAPB, 10 in QLB, 10 in P). In all groups MAP was higher than baseline at T2-T3-T4 time points (p < 0.05), in P group MAP also increased at T1 (p < 0.05). The incidence of CR at T1 was higher in P (70%) compared to TAPB (0%) and QLB (20%) (p = 0.001). No patient received postoperative rescue analgesia.ConclusionBoth TAPB and QLB guaranteed adequate analgesia regarding the somatic stimulus (T1) compared to P whereas all groups were not able to prevent a cardiovascular response during the induction of capnoperitoneum (T2) and ovarian traction (T3–T4). Analgesia in the early postoperative period (up to 4 h) was adequate in all groups.